Design And Simulation Of Cmos-Based Low Voltage Variation Bandgap Reference Voltage Circuitry Using 0.18μm Process Technology - Tan, Chee Yong (2015)

(untitled)
Nowadays, electronics that are able to operate reliably in harsh environments,especially in high temperature environments are in great demand. Electronic systems functioning at extreme temperature requires cooling or heating mechanism from external source. Those thermal management approaches will induce more circuitries into the system and increase the complexity of the overall system. Thus, it is necessary to eliminate the external thermal management circuit and at the same time, ensure that the sensors can operate at wide range of temperature. In this project, Bandgap Reference (BGR) circuit,which are found in on-chip circuitry, is used to produce a constant voltage regardless of temperature, process and supply voltage change. A wide temperature range, which is - 50oC to 140oC, and low voltage variation (1.85mV) of BGR circuit was designed and simulated using Cadence software. The BGR circuit was designed using CMOS compatible process in 0.18μm process technology. A two-stage Operational Amplifier (Op-amp) circuit was designed and incorporated into the complete BGR circuit. The operational amplifier and BGR circuits were simulated using DC and AC analysis in Cadence software. From the graphs plotted, it is found that the BGR circuit proposed is able to operate well at temperature from -50oC to 140oC with only 1.85mV of voltage variation. The proposed circuit has 38.9dB of PSRR and 7.9ppm/oC of Temperature Coefficient. Simulation results are also compared with some state-of-the-art BGR circuits.